#### Answer

$-6t+1$

#### Work Step by Step

We are given that $f(x)=-3x+4$. In order to evaluate the function at $2t+1$, we can plug in $2t+1$ to the function and evaluate directly.
$f(2t+1)=-3(2t+1)+4=(-3)(2t)+(-3)(1)+4=-6t-3+4=-6t+1$

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

$-6t+1$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.